Perlindungan HAM Terhadap Anak Perempuan yang Mengalami Female Genital Mutilations - Al-Azmi Nur Fadhilah Syarip; Muhammad Husni Syam; Syahrul Fauzul Kabir (Jurnal Riset Ilmu Hukum, 2023)
Abstract. This practice of FGM is very dangerous and can cause health problems to the point of triggering mental health, reducing or eliminating recognition, and enjoyment or execution of women. This study aims to understand how international human rights provide protection for girls who experience FGM and to understand the implementation of FGM practices in Indonesia and the UK. This study uses a normative juridical method, with bibliographical data or secondary data which includes primary, secondary and tertiary legal materials. The results obtained are: (1) Special international agencies such as WHO and the CEDAW convention observe that the practice of female circumcision is a traditional practice that is dangerous and can affect women's health, therefore the Committee on the Elimination of Discrimination Against Women issued General Recommendation no. 14: Female Circumcision in 1990 in an effort to protect women in the practice of FGM. And the Convention on the Rights of the Child which provides protection for children who experience FGM by providing recommendations to the state to eliminate traditional habits that harm children's health (2) The implementation of FGM practices in Indonesia is based on culture or religion while the implementation of FGM practices in England is carried out by someone who migrated to the UK and brought the FGM culture with them. Abstrak. Praktik FGM ini sangat berbahaya dan bisa menyebabkan masalah kesehatan hingga memicu kesehatan mental, mengurangi atau meniadakan pengakuan, dan penikmatan atau pelaksanaan terhadap perempuan. Penelitian ini bertujuan untuk memahami bagaimana hak asasi manusia internasional dalam memberikan perlindungan terhadap anak perempuan yang mengalami FGM serta untuk memahami implementasi praktik FGM di Indoneia dan Inggris. Penelitian ini menggunakan metode yuridis normatif, dengan data kepustakaan atau data sekunder yang mencakup bahan hukum primer, sekunder dan tersier. Hasil yang diperoleh yakni: (1) Badan-badan khusus internasional seperti WHO dan konvensi CEDAW mengamati bahwa praktik sunat perempuan merupakan praktik tradisional yang berbahaya serta dapat mempengaruhi kesehatan perempuan, maka dari itu Committee on the Elimination of Discrimination Againts Women mengeluarkan General Recomendation No. 14: Female Circumision in 1990 dalam upaya melindungi perempuan dalam praktik FGM. Dan Konvensi Hak Anak yang memberikan perlindungan terhadap anak yang mengalami FGM dengan memberi rekomendasi kepada negara untuk menghapuskan kebiasaan-kebiasaan tradisional yang merugikan kesehatan anak (2) Implementasi praktik FGM di Indonesia berdasar pada budaya atau agama sedangkan impelemntasi praktik FGM di Inggris dilakukan oleh seseorang yang bermigrasi ke negara Inggris dan membawa budaya FGM.